The Impact of market, performance and business-specific factors on the efficiency of structured commodity trade finance - Njoroge, Dennis (Strathmore University, 2020)
Studies conducted by various researchers have found a link between the profitability of a firm and its working capital management policies as the policies have an impact on the cost of working capital. As part of working capital management, firms borrow to cover temporary gaps in cash. There are a number of banking products available to firms that wish to borrow. This study sought to assess the impact of Market Factors, Performance based Factors, and Business-specific Factors on the effectiveness of structured commodity trade finance. The population for this study was the 42 licensed banks in Kenya. The sample for the study was all the banks that are classified in the large peer group by the Central Bank of Kenya as well as global banks that are not in the large peer group but that operate in Kenya. Primary data was collected through questionnaires issued to bankers and borrowers. A correlation analysis model employing the use of Spearman’s rank correlation model was used to analyse the data. Findings from this study indicate that there were no strong correlations between the dependent variable, effectiveness of the lending approach, and market factors, product specific factors, and customer and credit-specific factors. The only significant relationships observed were those between market factors and business-specific factors. The general inference, therefore, was that the various factors did not have an impact on the effectiveness of the lending approach.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Structured commodity; Trade finance; Business factors